Porous ceramic atomizing core, preparation method thereof and electronic cigarette
By using raw materials such as ceramic powder and zirconium acetate solution, the growth direction of ice crystals is controlled, and a porous ceramic atomized core with uniform pore size is prepared, which solves the problem of inconsistent micropore structure of the electronic cigarette atomized core matrix, and improves the user experience and quality of the product stability.
Patent Information
- Application Number
- CN202411402914.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-27
AI Technical Summary
The micropore structure of the existing electronic cigarette atomized core matrix is inconsistent, resulting in poor core paste or oil leakage during use of the product, and it is difficult to detect it in time in quality testing, affecting product reputation and industry development.
The porous ceramic atomized core is prepared by using ceramic powder, dispersant, adhesive and zirconium acetate solution as raw materials. The zirconium acetate molecules are adsorbed with the ice crystal surface through hydrogen bonds to control the growth direction of ice crystals. , forming a hexagonally symmetrical crystal morphology to ensure consistency of the pore structure.
The pore size distribution uniformity of the porous ceramic atomized core is achieved, the impact of microstructure defects on electronic cigarettes is avoided, and the product experience and quality stability is improved.
Smart Images

Figure CN119184381A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a porous ceramic atomization core and a preparation method thereof, as well as an electronic cigarette. Background Art
[0002] In the prior art, the atomizer core matrix of the electronic cigarette is cotton or ceramic. Cotton is woven from natural cotton materials, and ceramic is sintered from powder raw materials. Both materials are easy to obtain, affordable, and have excellent performance. However, the atomizer core matrix made of the above two materials is prone to microscopic defects. The microscopic defects include that the pore structure of the atomizer core matrix is irregular at the microscopic scale; its irregularity is manifested in the pore size, irregular arrangement of large and small pores, and occasional occurrence of very individual pores with pore sizes exceeding three or four times the average pore size. However, this kind of microscopic defect cannot be reflected in the macroscopic indicators, and it is not easy to be detected during the quality inspection process, and the cartridges mistakenly judged as qualified products flow into the market, causing consumers to experience the undesirable phenomenon of core sticking or oil leakage when using it. Although it is a low-probability event that e-cigarettes are mistakenly judged as qualified products and enter the market, with the increase in market demand for e-cigarettes, and the upcoming billions or even tens of billions of e-cigarettes, there will be hundreds of thousands of unqualified cartridges circulating in the market, which will have a negative impact on the reputation, image, brand rating, and even industry development of e-cigarettes.
[0003] Therefore, it is very important to solve the inconsistency of the microscopic pore structure of the atomizer core matrix and eliminate the defective product phenomenon of e-cigarettes caused by excessive pore size from the root. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide a porous ceramic atomization core and a preparation method thereof, as well as an electronic cigarette.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides a porous ceramic atomization core, the raw materials for its preparation include ceramic powder, dispersant, adhesive and zirconium acetate solution; the raw materials are mixed to obtain ceramic slurry, and the obtained ceramic slurry is freeze-cured, freeze-dried and sintered in sequence to obtain a porous ceramic matrix; then, heating circuits and electrodes are printed on a preset surface of the porous ceramic matrix to obtain a porous ceramic atomization core; in the raw materials, the added amount of the ceramic powder is 20 vol.% of the volume of the zirconium acetate solution, the added amount of the dispersant is (0.6-1) vol.% of the volume of the zirconium acetate solution, and the added amount of the adhesive is 1-3wt% of the added amount of the ceramic powder.
[0007] Optionally, the concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
[0008] Optionally, the ceramic powder includes zirconium oxide ceramic powder.
[0009] Optionally, the adhesive is a PVA-PEG composite adhesive obtained by mixing polyvinyl alcohol (PVA) and polyethylene glycol (PEG); wherein the ratio of the added amounts of polyvinyl alcohol and polyethylene glycol in the PVA-PEG composite adhesive is 1-5:1.
[0010] Optionally, the polyvinyl alcohol includes PVA505; the polyethylene glycol includes PEG4000.
[0011] Optionally, the dispersant comprises DOLAP IX dispersant.
[0012] Optionally, the DOLAP IX dispersant includes a mixture of a DOLAP IX CE64 dispersant and a DOLAP IX CA dispersant, wherein the volume ratio of the DOLAP IX CE64 dispersant to the DOLAP IX CA dispersant is (6-8):(2-4).
[0013] In a second aspect, the present invention provides a method for preparing a porous ceramic atomizing core, comprising the steps of:
[0014] S1. Prepare ceramic slurry; provide raw materials for preparation, and mix the raw materials to obtain ceramic slurry; the raw materials for preparation include ceramic powder, dispersant, adhesive and zirconium acetate solution, wherein the amount of the ceramic powder added is 20 vol % of the volume of the zirconium acetate solution, the amount of the dispersant added is (0.6-1) vol % of the volume of the zirconium acetate solution, and the amount of the adhesive added is 1-3 wt % of the amount of the ceramic powder added;
[0015] S2, freezing and solidification molding: freezing the ceramic slurry obtained in step S1;
[0016] S3, freeze drying; sublimating the ceramic slurry after freeze solidification and forming in step S2, removing the solidified phase in the ceramic slurry, and obtaining a porous ceramic atomization core green body;
[0017] S4, sintering; placing the porous ceramic atomization core green body obtained in step S3 into a sintering furnace for sintering to obtain a porous ceramic matrix;
[0018] S5: preparing heating circuits and electrodes; printing the heating circuits and electrodes on a preset surface of the porous ceramic substrate to obtain a porous ceramic atomization core.
[0019] Optionally, the concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
[0020] In a third aspect, the present invention provides an electronic cigarette, comprising a ceramic atomization core obtained by the preparation method as described above or a ceramic atomization core as described above.
[0021] The beneficial effects produced by the present invention include at least:
[0022] The raw materials for preparing the porous ceramic atomizer core of the present invention include ceramic powder, dispersant, adhesive and zirconium acetate solution. The zirconium acetate molecule includes two functional groups, hydroxyl group and acetate group. During the freezing and solidification molding process, the zirconium acetate ion is adsorbed on the surface of the ice crystal through the hydroxyl group to form a hydrogen bond with the hydroxyl group on the surface of the ice crystal, and the acetate group faces the inside of the ice crystal. The hydroxyl group and acetate group in the zirconium acetate molecule are adsorbed on the surface of the ice crystal. On the one hand, they form a protective film with the surface of the ice crystal through hydrogen bonds, which hinders the diffusion of water molecules to the surface of the ice crystal and slows down the adsorption rate of water molecules on the surface of the ice crystal, thereby controlling the growth direction of the ice crystal; on the other hand, the ice crystal grows along the C-axis direction to form a crystal morphology with hexagonal symmetry. The directional combination of the zirconium acetate molecule and the ice crystal prevents the adsorption of the surface of the water molecule, thereby controlling the growth of the ice crystal, ensuring the consistency of the formed pore structure, and avoiding the influence of microstructural defects on the final prepared electronic cigarette. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope test image of the porous ceramic atomization core obtained in the present invention.
[0024] Figure 2 The figure is a comparison diagram of the pore size distribution of the porous ceramic atomizer core obtained by the present invention and the ceramic atomizer core in the prior art. DETAILED DESCRIPTION
[0025] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in the present invention. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] It should be noted that the various component materials in the preparation raw materials described in the present invention can be sourced from suppliers known in the art, or can be prepared by known methods.
[0028] In a first aspect, the present invention provides a porous ceramic atomization core, the raw materials for its preparation include ceramic powder, dispersant, adhesive and zirconium acetate solution; the raw materials are mixed to obtain ceramic slurry, and the obtained ceramic slurry is freeze-cured, freeze-dried and sintered in sequence to obtain a porous ceramic matrix; then, heating circuits and electrodes are printed on a preset surface of the porous ceramic matrix to obtain a porous ceramic atomization core; in the raw materials, the added amount of the ceramic powder is 20 vol.% of the volume of the zirconium acetate solution, the added amount of the dispersant is (0.6-1) vol.% of the volume of the zirconium acetate solution, and the added amount of the adhesive is 1-3wt% of the added amount of the ceramic powder.
[0029] The raw materials for preparing the porous ceramic atomizer core of the present invention include ceramic powder, dispersant, adhesive and zirconium acetate solution. The zirconium acetate molecule includes two functional groups, hydroxyl group and acetate group. During the freezing and solidification molding process, the zirconium acetate ion is adsorbed on the surface of the ice crystal through the hydroxyl group to form a hydrogen bond with the hydroxyl group on the surface of the ice crystal, and the acetate group faces the inside of the ice crystal. The hydroxyl group and acetate group in the zirconium acetate molecule are adsorbed on the surface of the ice crystal. On the one hand, they form a protective film with the surface of the ice crystal through hydrogen bonds, which hinders the diffusion of water molecules to the surface of the ice crystal and slows down the adsorption rate of water molecules on the surface of the ice crystal, thereby controlling the growth direction of the ice crystal; on the other hand, the ice crystal grows along the C-axis direction to form a crystal morphology with hexagonal symmetry. The directional combination of the zirconium acetate molecule and the ice crystal prevents the adsorption of the surface of the water molecule, thereby controlling the growth of the ice crystal, ensuring the consistency of the formed pore structure, and avoiding the influence of microstructural defects on the final prepared electronic cigarette.
[0030] Optionally, the concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
[0031] After a large number of experiments, the inventors found that in the implementation of the technical solution of the present invention, only when the concentration of zirconium acetate reaches the level described in the present invention can sufficient coverage be formed on the surface of ice crystals, thereby playing a role in controlling the growth of ice crystals. During the freezing and solidification molding process, the hydroxyl groups and acetate groups in the zirconium acetate molecules adsorb on the surface of ice crystals, and on the one hand, form a protective film with the surface of ice crystals through hydrogen bonds, which hinders the diffusion of water molecules to the surface of ice crystals and slows down the adsorption rate of water molecules on the surface of ice crystals, thereby controlling the growth direction of ice crystals. This effect is most significant when the concentration of zirconium acetate solution reaches 0.065g / L.
[0032] Zirconium acetate can undergo the following forms of ionization in aqueous solution:
[0033] Form 1: Zr(OAc)4; under high pH conditions, Zr(OAc)4 will be completely ionized into Zr 4+and four acetate ions (Ac - ).
[0034] Form 2: Zr(OAc)30H; Under low pH conditions, Zr(OAc)4 will partially ionize to form a Zr 4+ ions and three acetate ions and one hydroxyl ion (OH - ).
[0035] Form 3: Zr(OAc)2OH2; when the pH value is further reduced, Zr(OAc)30H will continue to ionize and generate two Zr 3+ ion, two acetate ions, and two hydroxyl ions.
[0036] Form 4: Zr(OAc)OH3; at lower pH conditions, Zr(OAc)20H2 will continue to ionize to generate three Zr 2+ ion, one acetate ion, and three hydroxyl ions.
[0037] The concentration of zirconium acetate in aqueous solution can be adjusted by adjusting the pH value. 3+ ,Zr(OH)3OA,Zr(OH)3OA 2- proportion.
[0038] In the preferred pH range of 3-5 of the present invention, Zr(OH)3OA is the main component and is enriched. During the freeze-solidification molding process, its polymer will aggregate at the solid-liquid interface between water and ice, affecting the production structure of slurry ice crystals at the atomic level, causing the ice crystals to grow along the c-axis direction, forming a crystal morphology with hexagonal symmetry. This effect is more significant when the pH value of the zirconium acetate solution is in the range of 3.5-4.5.
[0039] Optionally, the ceramic powder includes zirconium oxide ceramic powder. The ceramic powder of the present invention is zirconium oxide ceramic powder, and the zirconium acetate solution in the preparation raw material forms zirconium oxide after sintering. The zirconium acetate solution can also be used as a zirconium source in the preparation process to provide zirconium oxide for the porous ceramic atomization core.
[0040] Optionally, the adhesive is a PVA-PEG composite adhesive obtained by mixing polyvinyl alcohol (PVA) and polyethylene glycol (PEG); wherein the ratio of the amount of polyvinyl alcohol to polyethylene glycol added in the PVA-PEG composite adhesive is 1-5:1. The adhesive in the present invention is a PVA-PEG composite adhesive, and before the PVA-PEG composite adhesive is added to the preparation raw material, a pretreatment step is also included: heating the PVA and PEG solutions at 80°C for 3h. Under the pretreatment conditions, the hydroxyl groups in PVA react with the hydroxyl groups in the larger molecular weight PEG to form a network structure. Since the PVA-PEG composite adhesive consumes functional groups that can form hydrogen bonds with water, the influence on the zirconium acetate mechanism is reduced, and the PVA-PEG network structure formed allows the green body to have a certain strength for demolding and sintering, thereby breaking through the original size limitation of the technology, so that it can obtain products with a synthetic height of more than 10mm, which meets the assembly requirements of various ceramic atomization cores.
[0041] Optionally, the polyvinyl alcohol includes PVA505, and the alcoholysis degree thereof is 87%-89%; and the polyethylene glycol includes PEG4000.
[0042] Optionally, the dispersant comprises DOLAPIX dispersant.
[0043] Furthermore, in some embodiments, the DOLAPIX dispersant includes a mixture of DOLAPIX CE64 dispersant and DOLAPIX CA dispersant, wherein the volume ratio of DOLAPIX CE64 dispersant to DOLAPIX CA dispersant is (6-8):(2-4).
[0044] Among them, DOLAPIX CE 64 dispersant is an alkali-free organic dispersant and deflocculating agent that does not produce foam; DOLAPIX CA dispersant is an organic dispersant that can be used with a variety of adhesives to improve the viscosity and stability of the slurry. The two are mixed to form a dispersant that can be used with adhesives and has the ability to produce an immediate deflocculating effect.
[0045] Furthermore, in some other embodiments, the raw material for preparation further includes an inorganic salt of yttrium, and the addition ratio of the inorganic salt of yttrium is Y 3+ Ions and Zr in zirconium acetate 3+ The ratio is Y 3+ :Zr 3+=56:1000 to 71:1000, so as to ensure that the yttrium oxide content of the final porous ceramic atomizer core product is between 2.8-3.5 mol%. The addition of the inorganic salt of yttrium forms yttrium oxide, which strengthens the zirconia ceramic to form a yttrium oxide-enhanced porous zirconia ceramic atomizer core matrix. The inorganic salt of yttrium includes one or more of Y(OAc)3, Y(C l)3 or Y(NO3)3.
[0046] In a second aspect, the present invention provides a method for preparing the porous ceramic atomizing core as described above, comprising the steps of:
[0047] S1. Prepare ceramic slurry; provide raw materials for preparation, and mix the raw materials to obtain ceramic slurry; the raw materials for preparation include ceramic powder, dispersant, adhesive and zirconium acetate solution, wherein the amount of the ceramic powder added is 20 vol % of the volume of the zirconium acetate solution, the amount of the dispersant added is (0.6-1) vol % of the volume of the zirconium acetate solution, and the amount of the adhesive added is 1-3 wt % of the amount of the ceramic powder added;
[0048] S2, freezing and solidification molding: freezing the ceramic slurry obtained in step S1;
[0049] In some embodiments, in step S2, the freeze solidification molding specifically includes the steps of: using a unidirectional freezing casting mold for casting, placing the cast mold on a pre-cooled copper mold, and freezing at a temperature of -80±2°C. The cooling rate of the mold is controlled by PID to be -10°C to -15°C / min, and the final insulation temperature is -40°C to -50°C. The complete freezing time is between 45-60 minutes, and the frozen sample is placed in a freeze dryer together with the mold for demolding.
[0050] S3, freeze drying; sublimating the ceramic slurry after freeze solidification and forming in step S2, removing the solidified phase in the ceramic slurry, and obtaining a porous ceramic atomization core green body;
[0051] In some embodiments, in step S3, the freeze-drying specifically includes the steps of: removing the solidified phase in the ceramic slurry after freeze-solidification in step S2 by sublimation to obtain a porous ceramic atomization core green body; wherein the freeze-drying time is 48-72h, the temperature of the cold trap is -60±2°C, the temperature of the sample stage is 50±2°C, and the drying air pressure is 0.1±0.1Pa.
[0052] S4, sintering; placing the porous ceramic atomization core green body obtained in step S3 into a sintering furnace for sintering to obtain a porous ceramic matrix;
[0053] In some embodiments, in step S4, the sintering specifically includes the steps of: placing the porous ceramic atomization core green body obtained in step S3 into a sintering furnace for sintering, and the temperature curve during sintering includes a first section: heating to 650°C at a heating rate of 1°C / min and keeping warm for 2 hours, a second section: heating to 1200°C at a heating rate of 5°C / min and keeping warm for 30 minutes, and a third section: heating to 1480-1530°C at a heating rate of 10°C / min and keeping warm for 2 hours.
[0054] S5: preparing heating circuits and electrodes; printing the heating circuits and electrodes on a preset surface of the porous ceramic substrate to obtain a porous ceramic atomization core.
[0055] Optionally, the concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
[0056] In a third aspect, an electronic cigarette comprises the porous ceramic atomization core as described above, or a porous ceramic atomization core obtained by the preparation method as described above.
[0057] Example 1
[0058] A porous ceramic atomizing core is prepared, wherein the raw materials include zirconium oxide ceramic powder, a dispersant, a PVA-PEG composite adhesive and a zirconium acetate solution; based on the total volume of the raw materials being 1 L, the amount of the zirconium oxide ceramic powder added in the raw materials is 20 vol %. of the volume of the zirconium acetate solution; the amount of the dispersant added is (0.6-1) vol %. of the volume of the zirconium acetate solution; and the amount of the adhesive added is 1-3 wt %. of the ceramic powder added; the concentration of the zirconium acetate solution is 0.65 g / L, and the pH value is 3-5.
[0059] The above-mentioned raw materials are mixed to obtain ceramic slurry, and the obtained ceramic slurry is freeze-cured, freeze-dried and sintered in sequence to obtain a porous ceramic matrix; then, heating circuits and electrodes are printed on a preset surface of the porous ceramic matrix to obtain a porous ceramic atomization core.
[0060] Optionally, the freeze solidification molding specifically includes the steps of: using a one-way freezing casting mold for casting, placing the cast mold on a pre-cooled copper mold for freezing at -80°C. The cooling rate of the mold is controlled by PID to be -10°C to -15°C / min, and the final insulation temperature is -40°C to -50°C. The complete freezing time is between 45-60 minutes, and the frozen sample is placed in a freeze dryer together with the mold for demolding.
[0061] Optionally, freeze drying specifically includes the steps of: removing the solidified phase in the ceramic slurry after freeze solidification molding by sublimation to obtain a porous ceramic atomization core green body; wherein the freeze drying time is 48h, the cold trap temperature is -60°C, the sample table temperature is 50°C, and the drying gas pressure is 0.1Pa.
[0062] Optionally, the sintering specifically includes the steps of: placing the porous ceramic atomization core green body obtained in the freeze-drying step into a sintering furnace for sintering to obtain a porous ceramic; wherein the sintering and temperature change curve in the sintering furnace is as follows: the first section: heating to 650°C at a heating rate of 1°C / min and keeping warm for 2h; the second section: heating to 1200°C at a heating rate of 5°C / min and keeping warm for 30min; the third section: heating to 1480-1530°C at a heating rate of 10°C / min and keeping warm for 2h.
[0063] Before adding the PVA-PEG composite adhesive to the preparation raw materials, a pretreatment step is also included: heating the PVA and PEG solution at 80° C. for 3 hours.
[0064] See also Figure 1 As shown, any porous ceramic atomizer core obtained by adopting the technical solution of the present invention is taken for microscopic morphology characterization, and the obtained scanning electron microscope test image can intuitively show that the pore structure inside the porous ceramic atomizer core obtained by the present invention is evenly distributed and the pore size is uniform.
[0065] Comparative Example 1
[0066] The electronic cigarette ceramic atomizer core in the prior art and the porous ceramic atomizer core obtained in the present invention were selected to perform particle size distribution tests on the pore structure. Among them, the electronic cigarette atomizer core in the prior art includes SF type atomizer core, SG type atomizer core and FC type atomizer core. Specifically, the SF type ceramic atomizer core refers to a ceramic atomizer core matrix prepared by an injection molding process using a ceramic slurry including diatomaceous earth, quartz sand, alumina, a pore-forming agent and glass powder; wherein, in terms of mass percentage, the SF type ceramic atomizer core matrix includes 30% diatomaceous earth, 20% quartz sand, 5% alumina, 15% pore-forming agent and 30% glass powder; and is prepared by a traditional hot casting method; the SG type ceramic atomizer core refers to a ceramic atomizer core matrix prepared by an injection molding process using a ceramic slurry including alumina and a pore-forming agent, and the specific composition ratio is 45% alumina and 55% pore-forming agent; the FC type ceramic atomizer core refers to a ceramic atomizer core matrix obtained by an ordinary freeze-casting process using pure alumina powder.
[0067] Test results see Figure 2As shown, the pore size of the microscopic pore structure of the porous ceramic atomizer core obtained by the present invention is distributed between 35-45μm, and the peak shape is sharp at about 40 microns, and the distribution peak value reaches 0.3, indicating that the pore size of the porous ceramic atomizer core obtained by the present invention is large and concentrated at about 40μm, and the size uniformity of the pore structure is improved. The pore size of the SF type ceramic atomizer core is distributed between 10-30μm, and the pore size is more concentrated in the range of 20-22μm, indicating that its overall pore size value is small. The pore size of the SG type ceramic atomizer core is distributed between 10-25μm, and the pore size is more concentrated in the range of 19-20μm. The pore size of the FC type ceramic atomizer core is distributed between 10-60μm, the pore size distribution range is large, and the pore size is more concentrated near 30μm.
[0068] Comparative Example 2
[0069] In Comparative Example 2, the SF-type ceramic atomizer core, SG-type ceramic atomizer core and FC-type ceramic atomizer core described in Comparative Example 1 and the ceramic atomizer core obtained by the present invention are used to prepare electronic cigarettes under the conditions of the same specifications, the same heating circuit and the same resistance value, and actual smoking tests are carried out for comparison. The smoking test comparison includes sweet-fragrance-explosive smoking tests as well as taste, anti-dry burning, anti-core sticking and anti-leakage tests.
[0070] The results of the sweet-fragrance-explosive smoking test are shown in Table 1. The score is 1-10 points. The higher the value, the better the smoking experience. The results of the taste, anti-dry burning, anti-core sticking and anti-oil leakage tests are shown in Table 2.
[0071] Table 1: Sweet-fragrance-explosive puff test data table of the porous ceramic atomizer core of the present invention and the ceramic atomizer core in the prior art.
[0072] Part Number Sweet / min Fragrance / min Burst / minute The porous atomizing core of the present invention 9 8 9 SG4 7 5 7 SF8 8 5 5 FC1 6 7 8
[0073] Table 2: Taste, anti-dry burning, anti-sticking and anti-oil leakage test data table.
[0074]
[0075] It can be seen from Table 1 that the ceramic atomizer core obtained by the present invention has a better sweet-fragrance-explosive puff test effect; it can be seen from Table 2 that the porous ceramic atomizer core of the present invention has excellent performance in taste and anti-dry burning, and also performs well in anti-core sticking and anti-oil leakage, and has a good product advantage.
[0076] Example 2
[0077] In this example, the amount of PVA-PEG composite adhesive added was used as a single variable to prepare a porous ceramic atomizer core using the preparation method described in Example 1. The amount of PVA-PEG composite adhesive added was 1wt% and 2wt% of the amount of ceramic atomizer core added.
[0078] Comparative Example 3
[0079] Compared with Example 2, the difference of Comparative Example 3 is that PVA303 adhesive is selected as the adhesive; wherein, the added amount of PVA303 adhesive is 1wt%, 2wt% and 4wt% respectively.
[0080] Test example:
[0081] The demoulding conditions and microstructures of the porous ceramic atomizer core obtained in Example 2 and the atomizer core obtained in Comparative Example 3 were tested during the preparation process. The test data are shown in Table 3. In Table 3, N / A indicates a state in which demoulding is impossible or the atomizer core is directly broken.
[0082] Table 3: Test table of the effects of different adhesives on the demolding and microstructure of the atomizer core.
[0083] Adhesive concentration Demolding Microstructure PVA-PEG composite adhesive 1wt% Unable to demould N / A PVA-PEG composite adhesive 2wt% Demolding Uniform structure PVA303 1wt% Unable to demould N / A PVA303 2wt% Unable to demould N / A PVA303 4wt% Demolding Structural disorder
[0084] As can be seen from Table 3, the porous ceramic atomizer core obtained in the present invention can be demoulded smoothly and has a uniform structure by using the PVA-PEG composite adhesive selected in the present invention and the preferred addition amount. This shows that the adhesive selected in the present invention is the PVA-PEG composite adhesive, and the hydroxyl groups in the PVA will react with the hydroxyl groups in the larger molecular weight PEG to form a network structure. Since the PVA-PEG composite adhesive consumes the functional groups that can form hydrogen bonds with water, the influence on the zirconium acetate mechanism is reduced, and the PVA-PEG network structure formed allows the green body to have a certain strength for demoulding and sintering, which meets the assembly requirements of various ceramic atomizer cores.
[0085] Example 3
[0086] In this embodiment, under the condition that the solid content of the ceramic slurry is 20%, the pH value of the zirconium acetate solution is 3, and the concentration of the zirconium acetate solution is used as a single variable to prepare a ceramic atomizer core. Among them, the concentrations of the zirconium acetate solution are 0.1g / L, 0.08g / L, 0.06g / L, 0.04g / L and 0.02g / L, respectively. In the process of preparing the ceramic atomizer core using the same preparation method as in Example 1, the ice crystal structure morphology formed during the freezing process was tested, and the test results are shown in Table 4. It can be seen from Table 4 that when the zirconium acetate concentration is ≤0.02g / L, the surface of the ice crystal shows a highly branched tree-like complex structure with a large surface roughness; when the zirconium acetate concentration is ≥0.08g / L, the surface of the ice crystal is completely transformed into an irregular form, and as the concentration increases, the effect on the surface morphology of the ice crystal is small.
[0087] Table 4: Test table of the effect of different zirconium acetate solution concentrations on ice crystal structure morphology.
[0088] Solid content Zirconium acetate concentration g / L pH form 20% 0.1 3 Irregular Cell 20% 0.08 3 Irregular Cell 20% 0.06 3 honeycomb 20% 0.04 3 honeycomb 20% 0.02 3 Tree Branch
[0089] Example 4
[0090] In this embodiment, under the condition that the concentration and pH of the zirconium acetate solution remain unchanged, the change of the solid content of the ceramic slurry is used to study the structural morphology of ice crystals formed when the slurry is frozen. The preparation method in this embodiment is the same as that in Example 1. The test results of the structural morphology of ice crystals are shown in Table 5. As can be seen from Table 5, when the solid content of the ceramic slurry is too small, the surface of the ice crystal presents a complex tree-like structure with a large surface roughness, and when the solid content of the ceramic slurry is too large, the slurry settles seriously and forms an irregular side morphology.
[0091] Table 5: Test table of the effect of changes in the solid content of ceramic slurry on the ice crystal structure morphology.
[0092]
[0093]
[0094] Example 5
[0095] In this embodiment, under the condition that the solid content of the ceramic slurry is 20%, the concentration and pH value of the zirconium acetate solution are used to study the structural morphology of ice crystals frozen in the ceramic slurry, and the research and test results are shown in Table 6. In this embodiment, the same preparation method as in Example 1 is used for preparation. It can be seen from Table 6 that within the preferred concentration and pH value range of the zirconium acetate solution of the invention, the surface of the ice crystals formed when the obtained ceramic slurry is frozen presents a regular honeycomb structure.
[0096]
[0097] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0098] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A porous ceramic atomizing core, characterized in that: The preparation raw materials include ceramic powder, dispersant, adhesive and zirconium acetate solution; the preparation raw materials are mixed to obtain ceramic slurry, and the obtained ceramic slurry is freeze-cured, freeze-dried and sintered in sequence to obtain a porous ceramic matrix; then, heating circuits and electrodes are printed on a preset surface of the porous ceramic matrix to obtain a porous ceramic atomization core; in the preparation raw materials, the addition amount of the ceramic powder is 20 vol.% of the volume of the zirconium acetate solution, the addition amount of the dispersant is (0.6-1) vol.% of the volume of the zirconium acetate solution, and the addition amount of the adhesive is 1-3%wt of the addition amount of the ceramic powder.
2. The porous ceramic atomizing core according to claim 1, characterized in that: The concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
3. The porous ceramic atomizing core according to claim 1, characterized in that: The ceramic powder includes zirconium oxide ceramic powder.
4. The porous ceramic atomizing core according to claim 1, characterized in that: The adhesive is a PVA-PEG composite adhesive obtained by mixing polyvinyl alcohol and polyethylene glycol; wherein the ratio of the added amounts of polyvinyl alcohol and polyethylene glycol in the PVA-PEG composite adhesive is 1-5:
1.
5. The porous ceramic atomizing core according to claim 4, characterized in that: The polyvinyl alcohol includes PVA505; the polyethylene glycol includes PEG4000.
6. The porous ceramic atomizing core according to claim 1, characterized in that: The dispersant includes DOLAPIX dispersant.
7. The porous ceramic atomizing core according to claim 6, characterized in that: The DOLAPIX dispersant includes a mixed solution of DOLAPIX CE64 dispersant and DOLAPIX CA dispersant, wherein the volume ratio of the DOLAPIX CE64 dispersant to the DOLAPIX CA dispersant is (6-8):(2-4).
8. A method for preparing the porous ceramic atomizing core according to any one of claims 1 to 7, characterized in that: Includes steps: S1. Prepare ceramic slurry; provide raw materials for preparation, and mix the raw materials to obtain ceramic slurry; the raw materials for preparation include ceramic powder, dispersant, adhesive and zirconium acetate solution, wherein the amount of the ceramic powder added is 20 vol.% of the volume of the zirconium acetate solution, the amount of the dispersant added is (0.6-1) vol.% of the volume of the zirconium acetate solution, and the amount of the adhesive added is 1-3wt% of the ceramic powder. S2, freezing and solidification molding: freezing the ceramic slurry obtained in step S1; S3, freeze drying; sublimating the ceramic slurry after freeze solidification and forming in step S2, removing the solidified phase in the ceramic slurry, and obtaining a porous ceramic atomization core green body; S4, sintering; placing the porous ceramic atomization core green body obtained in step S3 into a sintering furnace for sintering to obtain a porous ceramic matrix; S5: preparing heating circuits and electrodes; printing the heating circuits and electrodes on a preset surface of the porous ceramic substrate to obtain a porous ceramic atomization core.
9. The preparation method according to claim 8, characterized in that: The concentration of the zirconium acetate solution is 0.4-0.1 g / L, and the pH value is 3-5.
10. An electronic cigarette, characterized in that: The electronic cigarette comprises the porous ceramic atomization core as described in any one of claims 1 to 7, or the porous ceramic atomization core obtained by the preparation method as described in any one of claims 8 to 9.
